Locoregional Extension Patterns of Nasopharyngeal Carcinoma Detected by FDG PET/MR - Cao, Caineng; Xu, Yuanfan; Huang, Shuang; Jiang, Feng; Jin, Ting; Jin, Qifeng; Hua, Yonghong; Hu, Qiaoying; Chen, Xiaozhong (Frontiers in Oncology, 2021)
Purpose We sought to define the locoregional extension patterns of nasopharyngeal carcinomas (NPCs) by positron emission tomography (PET)/magnetic resonance imaging (MRI) and to improve clinical target volume (CTV) delineation. Methods Between May 2017 and March 2021, 331 consecutive patients with nonmetastatic NPCs who underwent pretreatment, simultaneous whole-body PET/MRI for staging were included in this study. Results The high-risk regions included the base of the sphenoid bone, the prestyloid compartment, prevertebral muscle, foramen lacerum, medial pterygoid plate, sphenoidal sinus, clivus, petrous apex, and foramen ovale. When the high-risk regions were invaded, the incidence rates of tumor invasion into the medium-risk regions increased. In contrast, when the high-risk regions were not involved, the incidence rates of tumor invasion into the medium-risk regions were mostly less than 10%, excluding the post-styloid compartment and oropharynx. According to the updated consensus guidelines of the neck node levels for head and neck tumors from 2013, level IIa (77.3%, 256/331), level IIb (75.8%, 251/331), and level VIIa (71.3%, 236/331) were the most frequently involved levels, followed by levels III (42.6%), Va (13.9%), IVa (8.8%), IVb (3.6%), Ib (3.6%), Vb (2.4%), VIIb (2.4%), VIII (1.8%), Vc (0.9%), and Xa (0.3%). Skip lymph node metastasis occurred in only 1.9% of patients. Conclusions For NPCs, primary disease and regional lymph node spread follow an orderly pattern, and a skip pattern of lymph node metastasis was unusual. Involved level radiotherapy might be feasible for cervical lymph node levels below the caudal border of cricoid cartilage and level VIIb.